Performance from birth to weaning of Santa Inês lambs born to ewes fed different levels of energy - Castro, Filipe Alexandre Boscaro de; Ribeiro, Edson Luis de Azambuja; Koritiaki, Natália Albieri; Mizubuti, Ivone Yurika; Silva, Leandro das Dores Ferreira da; Pereira, Elzânia Sales; Pinto, Andréa Pereira; Constantino, Camila; Fernandes Junior, Francisco (Semina: Ciências Agrárias, 2013)
The main objective of this study was to evaluate the influence of the energy levels in the diet of ewes in the last third of gestation and lactation on body measurements and weights of lambs from birth to weaning. As secondary objectives were also evaluated the effects of year of birth, sex of the lamb, type of birth and age of the ewe at lambing on the same characteristics. Forty-five Santa Inês lambs were evaluated. They were born from 40 ewes distributed randomly to three treatments: 2.0, 2.2 and 2.4 Mcal of metabolizable energy/kg of dry matter). Ewes were subjected to the experimental diets during the last third of gestation and lactation. Lambs were kept with their mothers until weaning, which occurred at 70 days. Feeding energy level did not affect traits measured on the lambs at birth. Regression analysis showed a linear increasing in all traits at weaning and in average daily gain until weaning as the energy level increased. Male lambs were heavier at birth and at weaning. All morphometric measurements performed were similar between males and females, except for thoracic perimeter at 70 days, which was higher in male lambs. Single lambs were larger and heavier than twin lambs. Lambs born from ewes of intermediate age (4 and 6 teeth) showed higher means for average daily weight gain. Among morphometric measurements, thoracic perimeter showed the best correlation to body weight at birth and at weaning. Besides the nutrition of the ewe, it is important to consider other environmental factors that affect animal's growth characteristics by acting on the expression of genetic potential.